Single-cell sequencing and transcriptome analyses in the construction of a liquid–liquid phase separation-associated gene model for rheumatoid arthritis - Tai, Jiaojiao; Wang, Linbang; Yan, Ziqiang; Liu, Jingkun (Frontiers in Genetics, 2023)
Rheumatoid arthritis (RA) is a disabling autoimmune disease that affects multiple joints.Accumulating evidence suggests that imbalances in liquid-liquid phase separation (LLPS) can lead to altered spatiotemporal coordination of biomolecular condensates, which play important roles in carcinogenesis and inflammatory diseases. However, the role of LLPS in the development and progression of RA remains unclear. This study aimed to identify the role of LLPS in the development of RA. We screened RA and normal samples from GSE12021, GSE55235, and GSE55457 transcriptome datasets and GSE129087 single-cell sequencing datasets from Gene Expression Omnibus database to investigate the pathogenesis of LLPS-related hub genes at the transcriptome and single cell sequencing levels. We used random forest trees, support vector machines, and weighted gene co-expression network analysis to screen out four and six LLPS-related genes and 396 Weighted correlation network analysis modular genes, respectively. Hybridization of the three groups revealed two hub genes, MYC and MAP1LC3B, that were validated using correlation studies. Our study reveals a possible mechanism for LLPS in RA pathogenesis and suggests that MYC and MAP1LC3B may be potential novel molecular markers for RA with immunological significance.